Cataloguing In Special Libraries In The 1990s - Elizabeth Makin; Nigel Ford; Alexander M. Robertson (Information Research: An International Electronic Journal)
Cataloguing in special libraries has been virtually ignored in the literature since the turn of the century, although there are many books and papers on cataloguing in general. It is not clear why this should be so, since it can be argued that the needs of special libraries are different from those of public, academic and national libraries. Special libraries are primarily interested in the information content of documents in the sense that they have little or no interest in documents except as "packages" in which information may be encapsulated. It is therefore reasonable to assume, a priori, that special libraries would undertake detailed indexing and light cataloguing, perhaps reducing the catalogue to the status of a finding list. This paper reports the results of a survey of current cataloguing practice in special libraries.